"It's not fiction, it's my life": LGBTQ+ youth of color and kinships in an urban school. Issue 1 (2nd January 2021) - Wozolek, Boni
ABSTRACT: This article argues that chosen family structures are critical for LGBTQ+ youth of color. Further, it articulates the inherent sense of agency that is found in choosing a family—something that not only shapes young ways of being, knowing, and doing but impacts their ability to resist toxic cultural norms that all too often position students for the school-to-prison and school-to-coffin pipelines. Finally, this article argues that schools should attend more closely to chosen family structures and find ways to include them in school culture to better sustain students, classrooms, and communities of color.